REVOLUTIONIZE EDUCATION WITH NEW TECHNOLOGY - Randhawa, Bhupinderjit kaur (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
Technology has revolutionized our society. In the last two decades, technology has dramatically penetrated into almost all walks of life and education was not an exception to it. The task of educating the young persons and students is not easy to perform. It needs large numbers of schools, colleges, universities and different kind of educational institutions, lots of funds and many other things. Universalization of elementary education is a cherished goal before our nation. Same is the case with our secondary education. In the age of globalization, our educational institutes need to be overhauled. New web-based technologies are becoming part and parcel of our education system. If the education needs to be qualitative, it should continuously be in track with the contemporary changes in the developments in the society.